2017
DOI: 10.5815/ijmecs.2017.04.04
|View full text |Cite
|
Sign up to set email alerts
|

A Network-Based Peer Evaluation Strategy

Abstract: Abstract-The purpose of this study was to design a network-based peer evaluation strategy -which included two types of peer evaluation (known and unknown) to investigate the effect of these two types on developing problem-solving and critical thinking skills for students in Java object oriented programming language course (OOP). The participants of this study were twenty-four (n=24) students at College of Science and Arts, Qassim university. The results revealed that the two types of peer evaluation (in both k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The researchers reported that the students 'motivation towards learning has been influenced by self-regulated learning strategies based on the electronic application. This result is consistent with the results of the studies of [20], [38], [39].…”
Section: Resultssupporting
confidence: 94%
“…The researchers reported that the students 'motivation towards learning has been influenced by self-regulated learning strategies based on the electronic application. This result is consistent with the results of the studies of [20], [38], [39].…”
Section: Resultssupporting
confidence: 94%
“…Students' interaction is important to improve understanding, self-confidence, and forming critical and creative thinking [10]. Two types of interactions that are often associated with relationships between students are friendships and peer tutors.…”
Section: Related Workmentioning
confidence: 99%
“…and student interaction with the learning content [9]. Peer-to-peer interaction provides mutual advantages for all participants and helps to improve understanding, self-confidence, and forming critical and creative thinking [10]. According to [11], peer-to-peer interaction is equally or more significant than the traditional teaching approach.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the concept of forming a labor market development policy (Figure 4) based on the definition of the main subjects of the management system, elements that determine the strategy for the development of human capital, the functions of state regulation and the main directions of building an educational strategy [14], we determined that the main stages of building a strategy are: the development of a regulatory framework within their competence [15]; the formation of goals, objectives and principles of the system for the development of professional competencies from IT, arising from the concept of economic development; analysis [16] and consideration of external factors; programming, including the development of a system of procedures, measures and personnel technologies; monitoring of "human resources" (implementation of specific measures and assessment of their effectiveness); control at all hierarchical management levels. The main subjects of the management system [17] are: public administration bodies, regional management bodies, personnel of divisions of the "Human Resources" Management System, Information and management relations and flows, the main methods of labor market management.…”
Section: Number Of the Unemployed In Thousands Of Peoplementioning
confidence: 99%